2016
DOI: 10.1158/1940-6207.capr-15-0300
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Atorvastatin on Breast Cancer Biomarkers in High-Risk Women

Abstract: Statins have the potential to reduce breast cancer incidence and recurrence as shown in both epidemiologic and laboratory studies. The purpose of this study was to evaluate the effect of a lipophilic statin, atorvastatin, on breast cancer biomarkers of risk [mammographic density (MD) and insulin growth factor 1 (IGF-1)] in high-risk premenopausal women. Premenopausal women at increased risk for breast cancer received either 40 mg of atorvastatin or placebo for 1 year. Biomarker assessment was performed prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Studies conducted with atorvastatin also show contradictory results. For example, in the study by Ji et al ( 22 ) biomarker assessments were not changed by atorvastatin application. However, more randomized clinical trials are needed to investigate these associations.…”
Section: Discussionmentioning
confidence: 94%
“…Studies conducted with atorvastatin also show contradictory results. For example, in the study by Ji et al ( 22 ) biomarker assessments were not changed by atorvastatin application. However, more randomized clinical trials are needed to investigate these associations.…”
Section: Discussionmentioning
confidence: 94%
“…Emerging research suggests that statins may prevent various types of cancers, including colon [182184] and breast [185187] as well as ovarian, pancreatic, lung, and lymphomas, reviewed in [188]. Statins inhibit cancer cell proliferation by arresting the cell cycle at the G 1 -S phase and inducing apoptosis [189, 190].…”
Section: The Yin – Yang Of No and H2s In Carcinogenesismentioning
confidence: 99%
“…These biological data have been confirmed in clinical studies. 115 Improved disease-free survivals have been demonstrated in breast cancer survivors and prostate cancer survivors taking statins. 116,117 Recently, a large study of more than 4000 veterans with multiple myeloma demonstrated a 12-month overall survival advantage in individuals with multiple myeloma on a statin.…”
Section: Cardiac Risk Factors and Cancer Outcomesmentioning
confidence: 99%